Growing Educators from Within: Human Resourse Strategy in Pesantren Leadership Development - Maemunah Maemunah; Suklani Suklani (JIEM (Journal of Islamic Education Management), 2025)
This study aims to analyze the impact of human resource management (HRM) strategies on the development of santri cadres as educators at Pondok Pesantren An-Nida. The research focuses on teacher planning, competency development, character formation, and performance evaluation. Using a qualitative approach through in-depth interviews, observations, and document analysis, the findings show that systematically implemented HRM strategies enhance the santri’s pedagogical competence, discipline, leadership qualities, communication skills, and sense of responsibility. Institutionally, these strategies support sustainable internal teacher regeneration and maintain educational quality at Pondok Pesantren An-Nida. This study concludes that value-based and professional HRM practices are essential for the successful cadre formation of future educators within the pesantren environment. Keywords: Human Resource Management, Santri Cadre Development, Educator Formation, Islamic Boarding School